Assessment of the Capital Structure and Cost of Capital Using Financial Indicators, the Case of Large Businesses in Albania - Luçi, Edlira; Phd Cand. Llesh Lleshaj, (European Journal of Multidisciplinary Studies, 2016)
The assessment of capital cost and capital structure is a complex field of financial activities, integrating all long term decisions of financial funding. Difficulties arise especially when financial markets are not liquid, as in the case of Albania, in terms of a new market that is economically, politically, legally, and fiscally fragile. The purpose of this paper is to assess the capital structure and cost of capital for large businesses in Albania that have a 100 percent Albanian ownership. Financial analyzes are based on the 2013-2014 financial statements of 50 companies, within 5 most representative sectors of the economy. The performed analyzes are based on multivariate regressions and the application of financial formulas. According to estimates in Albania, it results that companies do not have an optimal structure of capital, and furthermore the diversification of capital structure is merely a theoretical concept. Therefore, businesses face a high cost of capital. Even their level of systemic risk "beta" ranks them with more risk. Consequently, these businesses will not be able to achieve exports of goods and services to compete in international markets.
Keywords: optimal capital structure, cost of capital